Вироби ювелірного та декоративно-ужиткового мистецтва стародавнього Києва (за матеріалами розкопок Старокиївської експедиції 2001—2002 рр.) - Архипова, Є.І. (Археологія, 2006)
Статтю присвячено публікації виробів давньоруського ювелірного й декоративно-ужиткового мистецтва, знайдених у «місті Ярослава» в Києві. Статья продолжает публикацию материалов, исследованных в 2001—2002 гг. в западной части «города Ярослава»
(см. № 1 за 2006 г.). В ней анализируются изделия ювелирного и декоративно-прикладного искусства ХІ—ХVII І вв., представленные украшениями из серебра, медных и свинцово-оловянных сплавов и стекла. Значительная
часть находок (недорогие перстни, бубенчики, пуговицы, бусина «дреговичского» типа, бляшки, накладки и
пряжки ремней, булавки, писала, фрагмент привески-амулета в форме топорика и др.) древнерусского времени
изготовлена местными мастерами. Уникальны находки фрагментов византийских стеклянных браслетов с росписью эмалью Х — начала ХІІ в. и экзагия сирийского (?) происхождения. The article continues publication of materials studied in the western part of the «Yaroslav city» in 2001—2002 (see
issue No 1, 2006). The article analyses works of jewelry and arts and crafts of the 11th — 18th cc. represented by silver,
copper and leaden-tin alloys and glass objects. The majority of finds (cheap seal rings, small bells, buttons, a bead of the
«Drehovytskyj» type, plaques, plates and belt buckles, pins, stylos, fragment of an axe-shaped appendant-amulet, etc.)
of the Ancient Rus period were manufactured by the local craftsmen. There were several unique objects discovered:
fragments of Byzantine glass bracelets with enamel painted decoration, which date back from the 10th — early 12th c. and an
exagium of Syrian (?) origin.